Kandinsky e o espírito. Tempo, liberdade e vida na concepção kandinskyana da «vibração interior» - Justo, José Miranda (2016)
On the basis of Kandinsky’s article “On the Question of Form” (as well as passages of Concerning the Spiritual in Art), there arises the possibility of reconstructing the specific features of the artist’s concept of “pure inner vibration” in connection with the concept of the “spiritual”. These features include an important articulation of different modalities of time (hastiness, protracted time and suddenness), and a complex gradation of inner experience that starts with abstraction from external finality and ends with a criticism of subjectivity and a conception of inner universality, which – instead of being reducible to a logical procedure – indicates the exact place of singularity (and art) inside the structure of one’s experience.